A mixed method study for investigating critical success factors (CSFs) of E-learning in Saudi Arabian Universities - Naveed, Quadri Noorulhasan; Muhammad, AbdulHafeez; Sanober, Sumaya; Qureshi, Mohamed Rafik N.; Shah, Asadullah (The Science and Information (SAI) Organization, 2017)
Electronic learning (E-Learning) is the education system has becoms the obvious choice of the community over the blobe because of its numerous advantages. The main aim of the present study is to identify critical success factors (CSFs) and validate them for successful implementations of the e-leanring at Saudi Arabian Universtrs. This study developed a multidimentional instrument for mreasuring the E-Learning CSFs in the higher educationla institutions of Saudi Arabai. This study reviewed various CSFs from literature and identified most important E0-Learning CSFs which are described and grouped in five dimensions such as studnet, instructor, design and contents, system and technology, and institutional management services. The 36 CSFs falling under these relevant dimensions were then validated their importance quantitatively through university students, instructors, and e-learning staffs of some well-known universities in Saudi Arabia. A survey instrument was developed and tested on a sample of 257 respondents of Saudi Arabia Universities. It was found that systems and technological dimension is the most significant as perceived by respondents. Results of the study discovered that all obtained factors are highly reliable and thus would be useful to develop and implement e-learning system